2019
DOI: 10.1021/acssuschemeng.9b04453
|View full text |Cite
|
Sign up to set email alerts
|

Coal-Filler-Based Thermoplastic Composites as Construction Materials: A New Sustainable End-Use Application

Abstract: This paper reports investigations into coal's viability as an alternative filler to wood flour in wood plastic composites (WPCs)a class of materials used in building applications in lieu of pressure-treated wood coal plastic composites (CPCs) were fabricated with 15−60 wt % coal combined with high-density polyethylene and their physical (mechanical, water absorption, and metal leaching) and chemical (oxidative degradation and flammability) properties were compared with commercial WPCs. In addition, mass and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 53 publications
3
16
0
Order By: Relevance
“…Note, a previous study highlighted the antioxidation impact of coal on polymer composites. 14 Similar mechanisms for WPC decomposition under air were proposed in the literature. 13,28 Ignition temperatures of CPC FIT is the minimum temperature at which flammable volatiles released, due to heating of a material, ignites with the presence of a pilot flame.…”
Section: Tgasupporting
confidence: 52%
See 3 more Smart Citations
“…Note, a previous study highlighted the antioxidation impact of coal on polymer composites. 14 Similar mechanisms for WPC decomposition under air were proposed in the literature. 13,28 Ignition temperatures of CPC FIT is the minimum temperature at which flammable volatiles released, due to heating of a material, ignites with the presence of a pilot flame.…”
Section: Tgasupporting
confidence: 52%
“…Recently, several types of coal have been investigated to replace wood flour used in polymer composites. 14,15 A former study has shown that coal plastic composite (CPC) outperformed several commercially available WPC products in strength, oxidation, burn rate, ignition, and water absorption. 14 In addition, a preliminary life cycle analysis also indicated CPC manufacturing requires less energy and generates less greenhouse gas emissions than WPC manufacturing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among all composites, the 30L55WF-PA(N), containing 55% WF-PA(N) in the LDPE matrix, presented a flame spread rate of 16.06 mm/min. Generally, such phenomenon could be ascribed to the fire retardant fillers(WF-PA(N)) in polymer matrix (LDPE) that restrain composite combustion associated with char layer formation on the surface inhibiting internal layers from the external heating environment (Nicole et al, 2010;Umemura et al, 2014;Al-Majali et al, 2019). Therefore, it is clear that the addition of phytic acid modified wood (WF-PA(N)) not only can significantly improve in flame retardant properties, but help to reduce the carbon footprint of plastics through reusing wood flours to meet the environmental protection trends.…”
Section: Flame Retardancy Analysismentioning
confidence: 99%